⇒I will first isolate y together with its coefficient k by placing
to the right hand side...
![ky=x+t^(2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/cv4cf0pjuji7cbu6nt3eqee3jldsjfgju6.png)
⇒Now to leave y independent we have to divide ky by the coefficient of y which in this case is k.
⇒Meaning k will divide all the terms in the equation.
![(ky)/(k) =(x)/(k) +(t^(2))/(k) \\y=(x)/(k) +(t^(2))/(k)](https://img.qammunity.org/2023/formulas/mathematics/high-school/hm9gkqzlbzdmmhdwl33xmrcgtk716dq0w7.png)
⇒Attached is the answer.